2015
DOI: 10.1177/0363546515617468
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Patient-Reported Outcomes of Debridement or Microfracture of Concomitant Full-Thickness Cartilage Lesions in Anterior Cruciate Ligament–Reconstructed Knees

Abstract: MF of concomitant full-thickness cartilage lesions showed adverse effects on patient-reported outcomes at 2-year follow-up after ACL reconstruction. Debridement of concomitant full-thickness cartilage lesions showed neither positive nor negative effects on patient-reported outcomes at 2-year follow-up after ACL reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 37 publications
1
23
0
1
Order By: Relevance
“…This patient cohort has previously been described in a study on the effects of surgical debridement or MF of concomitant full-thickness cartilage lesions on 2-year patient-reported outcomes. 24…”
Section: Methodsmentioning
confidence: 99%
“…This patient cohort has previously been described in a study on the effects of surgical debridement or MF of concomitant full-thickness cartilage lesions on 2-year patient-reported outcomes. 24…”
Section: Methodsmentioning
confidence: 99%
“…Røtterud et al demonstrated in knees undergoing anterior cruciate ligament reconstruction with associated grade 3 to 4 cartilage defects that no treatment of the lesion or simple debridement gave better long-term results than microfracture. 18 Whether these findings can be extrapolated to a large patient population or to the hip again is unknown.…”
Section: Arthroscopic Debridementmentioning
confidence: 99%
“…Auch wenn weiterführende Untersuchungen zur Hüfte noch ausstehen, deuten die hier beschriebenen Erkenntnisse und Ergebnisse darauf hin, dass knochenmarkstimulierende Verfahren verschiedene biologische Defizite aufweisen, die auch im Hüftgelenk beobachtet werden können und die als problematisch gelten [45,72,96,97]. Unabhängig vom Gelenk sollte das Ziel einer biologischen Knorpelrekonstruktion die Wiederherstellung eines Knorpelgewebes sein, das in seiner Zusammensetzung, Struktur und Funktion dem gesunden hyalinen Knorpel möglichst nahekommt [64,98].…”
Section: Biologische Erkenntnisse Und Allgemeine Aspekte Zu Verschiedunclassified